The Relationship Between Employee Job Satisfaction And Employee Performance At Rsu X Jombang: A Cross-Sectional Study - Resi Lystianto Putra Perdana; Mochmad Mockhlas; Musa Ghufron (Global Journal of Health Administration, 2025)
Objective:Human resources represent a fundamental strategic asset in healthcare organizations, where job satisfaction significantly influences employee performance and patient care quality. Despite its critical importance, many hospitals continue to report suboptimal job satisfaction levels, particularly regarding compensation, career development, and work environment conditions  Method: This research is a qualitative research with a cross-sectional approach. This study aimed to analyze the relationship between job satisfaction and employee performance at RSU X Jombang, East Java, Indonesia. This study utilized validated questionnaire instruments that had been previously ethically approved and published in prior research by subahtiyar at 2020. Written informed consent was obtained from all participants prior to data collection. Data was collected using a questionnaire based on a Likert scale, and analyzed using logistic regression.  Result : Respondents demonstrated moderate overall job satisfaction (58.70%) and good performance levels (61.83%). The highest satisfaction was observed in salary (61.30%) and promotion (60.20%) dimensions. Logistic regression revealed that only promotion opportunities significantly influenced employee performance (p=0.043; OR=3.118; 95% CI: 1.036-9.385), while other dimensions showed non-significant relationships.  Conclusion: This study provides empirical evidence on the relationship between job satisfaction and employee performance within the context of regional public hospital settings in Indonesia, specifically at RSU X Jombang